Corporate governance : an empirical study of Malaysian companies - Neo, Roslyn Hui Zhi (2008)
This paper investigates the association between corporate governance structure, firm performance and corporate leverage in Malaysia. Our results indicate that leverage is negatively associated with common equity ownership concentration and positively associated with board independence. We find that corporate governance structure affects firm performance. Specifically, we find that firm performance is positively associated with equity ownership concentration.